Descriptive Study of a Cohort of 488 Patients with Inherited Retinal Dystrophies - Coco-Martin RM; Diego-Alonso M; Orduz-Montaña WA; Sanabria MR; Sanchez-Tocino H (Clinical Ophthalmology, 2021)
Rosa M Coco-Martin,1,2 Miguel Diego-Alonso,1,3 W Andres Orduz-Montaña,1 M Rosa Sanabria,1,4 Hortensia Sanchez-Tocino1,3 1Instituto Universitario de Oftalmobiología Aplicada (IOBA), University of Valladolid, Valladolid, Spain; 2Red Temática de Investigación Cooperativa en Salud de Oftalmologia (Oftared), Instituto de Salud Carlos III, Madrid, Spain; 3Department of Ophthalmology, Hospital Universitario Río Hortega, Valladolid, Spain; 4Department of Ophthalmology, Complejo Hospitalario De Palencia, Palencia, SpainCorrespondence: Rosa M Coco-MartinInstituto de Oftalmobiologia Aplicada (IOBA), University of Valladolid, Campus Miguel Delibes, Pº de Belén Nº 17, Valladolid, 47011, SpainTel +34 983423559, ext. 4738Fax +34 983423274Email rosa@ioba.med.uva.esPurpose: To analyze the distribution of inherited retinal diseases (IRDs), describe the clinical characteristics of patients, and determine the percentages of patients with genetic diagnosis in the Castilla y Leon region of Spain.Methods: All patients with an IRD seen in the two major referral units of Castilla y Leon during a 20-year period were included. The ages at symptom onset, diagnosis, and the last visit; sex; family history; history of consanguinity; type of inheritance; status of the fundus and electroretinogram findings; lens and macular status, visual acuity; and visual field data were recorded. Patients were divided into those with retinitis pigmentosa (RP) and all others. Gene mutations were gathered when available.Results: Four hundred eighty-eight patients with IRDs were studied: 216 (44.26%) with RP of which 34 (15.74%) had syndromic diseases, and 272 had other conditions being 161 (59,19%) macular dystrophies. The mean delay in diagnosis was 6– 16.2 years respectively. For the RP group the mean age at the last visit was 47.96± 17,26; mean age of cataract surgery was 48.30 ± 12.01 years; and the foveal area was preserved in 74 (35.07%) patients, atrophic in 101 (47.87%), and edematous in 36 (17.06%). A genetic study had been performed in 58 (26.85%) of patients with RP and 71 (26,1%) of the rest, being indeterminate in 17 (29.31%) out of RP group and 20 (28.16%) out of the others.Conclusion: Clinical characteristics are comparable to other published series. There is a significant delay in diagnosis. The number of patients with IRDs and available genetic diagnosis, thus being possible candidates for undergoing personalized treatments including gene therapy in our region is low and must be improved.Keywords: inherited retinal dystrophies, retinitis pigmentosa, genetic diagnosis, visual acuity, visual field